Framing War and Peace Narratives: A Corpus Based Study ofNetanyahu and Pezeshkian’s UNGASpeeches2024 (Journal of Asian Development Studies, 2024)
This study examines the speeches of Prime Minister Benjamin Netanyahu and President Masoud Pezeshkian at the 2024 United Nations General Assembly (UNGA). It employs both corpus and computational linguistic techniques to analyse linguistic patterns, themes, and frames. It examines how each leader frames war and peace narratives through the use of keywords, concordance, and frequency analysis. Netanyahu positions Israel as a peacemaker and Iran as a global threat by labelling his opponents as alleged sponsors of terrorism. On the other hand, Pezeshkian highlights how his nation is being victimised by external aggression and facing imposed sanctions. He frames Iran as an actor advocating for justice and Israel as actively involved in establishing Western hegemony. The comparative framing analysis emphasises how discourse is used as a geopolitical tool to shape international perceptions, legitimise national policies, and expand alliances globally. Hence, this research offers insights into the polarisation of Israeli and Iranian discourse by highlighting their respective linguistic strategies. The use of specific lexical choices reflects broader ideological stances and aligns with their respective foreign policy goals. This corpus-based study effectively reveals that war and peace are not merely political realities but also discursive constructions shaped and reshaped through rhetorical strategies on global platforms, such as the UNGA.